(untitled) (Географический вестник=Geographical bulletin, 2017)
Дается краткая характеристика опасных природных метеорологических явлений на территории Архангельской области, предлагаются возможные меры борьбы с ними. DANGEROUS WEATHER PHENOMENAS AS FACTOR OF NATURAL RISKS ON TERRITORY OF THE ARCHANGELSK AREA Dangerous weather phenomena, which are existed on theterritoryofArchangelskarea for period 1966-2005 years, are considered. Their repeatability and spreading on the territory are analyzed. The most typical periods and regions are revealed in distribution for each dangerous phenomenon.